Application of a test of basic gymnastic ability to identify potential talents y artistic gymnastics in the generic phase of adaptation and initiation to the physical activity - López J.; M. Vernetta (Asociación Española de Ciencias del Deporte, 2010)
The fundamental objective of this study consists of a test of basic gymnastic ability (in the form of a closed circuit), that could be certified as the starting point that identifies the potential subject sportsman / woman in power, with the specific motor motor profile. The test of ability designed was valued in function of the time and also through systematic observation by means of an expert that would issue a subjective valuation. The test was applied to a total of 592 subjects of both sexes from the province of Granada (Spain) between the ages of 6 and 12. Furthermore, the motor skills section of the Eurofit battery test was undertaken for several cineanthrometric measurements. The results seem to confirm the reliability of the time test and an important correlation with the expert´s valuation. These tests require means very elemental and, at the same time, the coach the can apply this test in a simple and effective way. KEY WORDS: Artistic Gymnastics, Detection, Talent, Eurofit.